Peran Etika Bisnis dan Kualitas Produk Terhadap Kepercayaan Konsumen: Studi Kasus Pabrik Aice - Alfi Nura; Shela Azzahra Tongku; Ghania Fayyaza Siregar; Nayla Dentisa; Azelia Inggrid Sugita; Dina Khairiyah; Silvia Aulia Situmeang (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2026)
Currently, the business landscape is experiencing a significant surge in the number of entrepreneurs, resulting in increasingly fierce, competitive market conditions. This intense competition requires businesses to consistently innovate and deliver high-quality products to attract customers and ensure profitability. However, success in the business world is not solely determined by financial gains; the ethical conduct of business operations is equally, if not more, critical. Good business ethics can significantly enhance business ventures, contributing to a strong reputation and sustained success. This research aims to thoroughly analyze the crucial role of business ethics and product quality in influencing consumer trust, using a specific case study of the Aice Factory. The study is a qualitative research study. Qualitative data was meticulously gathered through open questionnaires, capturing insights from interviews conducted with 43 AICE consumers. This approach enabled a deep exploration of consumer perceptions and experiences of Aice's products and ethical practices. Based on a comprehensive analysis of the research results, it is evident that both Aice's business ethics and the quality of its products play a profoundly important role in shaping and maintaining consumer trust. Consumers consistently prefer companies that demonstrate a strong commitment to ethical business practices and deliver on product quality. High product quality directly contributes to consumer satisfaction and builds confidence, while sound business ethics helps to cultivate a positive corporate image and strengthens consumer loyalty. Therefore, this research emphatically confirms that business ethics and product quality are indispensable and interconnected pillars in building consumer trust. Ultimately, a strong foundation of trust positively impacts Aice Factory's long-term sustainability and growth in a highly competitive market environment